2017
DOI: 10.5194/tc-11-971-2017
|View full text |Cite
|
Sign up to set email alerts
|

Surface-layer turbulence, energy balance and links to atmospheric circulations over a mountain glacier in the French Alps

Abstract: Abstract. Over Saint-Sorlin Glacier in the French Alps (45 • N, 6.1 • E; ∼ 3 km 2 ) in summer, we study the atmospheric surface-layer dynamics, turbulent fluxes, their uncertainties and their impact on surface energy balance (SEB) melt estimates. Results are classified with regard to largescale forcing. We use high-frequency eddy-covariance data and mean air-temperature and wind-speed vertical profiles, collected in 2006 and 2009 in the glacier's atmospheric surface layer. We evaluate the turbulent fluxes with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Vionnet et al, 2012) and the turbulent fluxes (e.g. Litt et al, 2017). In fact, each component of the turbulent fluxes (H and LE) simulated with original SAFRAN wind data is lower than those simulated with the measured wind.…”
Section: Sensitivity To Wind Speed Correctionmentioning
confidence: 87%
See 3 more Smart Citations
“…Vionnet et al, 2012) and the turbulent fluxes (e.g. Litt et al, 2017). In fact, each component of the turbulent fluxes (H and LE) simulated with original SAFRAN wind data is lower than those simulated with the measured wind.…”
Section: Sensitivity To Wind Speed Correctionmentioning
confidence: 87%
“…This underestimation is likely due to both non-consideration of katabatic wind and local effects due to orography (Dumont et al, 2012). As mentioned in Litt et al (2017), when large-scale atmospheric forcing was strong, intense downslope winds were observed, aligned with the main glacier flow (i.e. coming from the south; see Fig.…”
Section: Adjusted Safran Datamentioning
confidence: 89%
See 2 more Smart Citations
“…Similar campaigns have targeted icecaps in Iceland (Oerlemans et al., 1999; Reuder et al., 2012) and the melting edge of the Greenland Ice Sheet (van den Broeke et al., 1994). Observations of wind speed and temperature gradients within the lowest few meters of the glacier SBL have been made in various locations (e.g., Litt et al., 2017; Munro & Davies, 1977; Sicart et al., 2014) and have shown that the validity of bulk aerodynamic methods used to model turbulent heat fluxes depends on the proximity of a wind speed maximum to the glacier surface and the extent to which large‐scale winds influence the glacier SBL (e.g., Litt et al., 2015; Radic et al., 2017; Smeets et al., 1998, 2000). Observations of spatial and temporal variations in surface meteorology, most commonly air temperature, have also been made over many glaciers (e.g., Ayala et al., 2015; Greuell & Böhm, 1998; Petersen & Pellicciotti, 2011; Shea & Moore, 2010), with some studies showing that spatial variability is often linked to different wind flow regimes.…”
Section: Introductionmentioning
confidence: 99%